Membudayakan Rutinitas Majelis di Lingkungan Masyarakat dalam Memupuk Keselarasan Beragama Desa Bermi Kabupaten Probolinggo - Arisanti , Kustiana; Yasin, M.Ali; Hadi, Samsul; Hendarto, Kacong (Kalam Nusantara Institute, 2024)
The activity in carrying out this activity is a form of mentoring that has been carried out by members of some of students and lecture of Zainul Hasan Islamic University of Genggong in various assembly activities in Bermi village, from science assemblies to routine assemblies. From the observations we found, Bermi village has a lack of specific religious knowledge in the field of corpse management, even though Bermi village has many assemblies. The result of this activity is to increase assembly activities in Bermi village to foster views in religious knowledge for the entire Bermi village community.